2013
DOI: 10.1088/0029-5515/53/10/104017
|View full text |Cite
|
Sign up to set email alerts
|

Overview of results from the MST reversed field pinch experiment

Abstract: An overview of recent results from the MST programme on physics important for the advancement of the reversed field pinch (RFP) as well as for improved understanding of toroidal magnetic confinement more generally is reported. Evidence for the classical confinement of ions in the RFP is provided by analysis of impurity ions and energetic ions created by 1 MW neutral beam injection (NBI). The first appearance of energetic-particle-driven modes by NBI in a RFP plasma is described. MST plasmas robustly access the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…Furthermore, s ¼ 6:2 ms is close to the fast-ion confinement time measured from lowbeam concentration (no excitation of instabilities) experiments using the beam blip method. 29 As in Figure 2(b), the classically predicted core fast ion density saturates at $2:5 Â 10 18 m À3 after $18 ms injection (40 A), which is $25% of the core electron density (n e0 $ 1 Â 10 19 m À3 ). In reality, however, the core fast ion density is expected to be below the classical prediction, as instabilities occur $2:5 ms after beam injection (Sec.…”
Section: A Fast-ion Distribution Modelingmentioning
confidence: 68%
“…Furthermore, s ¼ 6:2 ms is close to the fast-ion confinement time measured from lowbeam concentration (no excitation of instabilities) experiments using the beam blip method. 29 As in Figure 2(b), the classically predicted core fast ion density saturates at $2:5 Â 10 18 m À3 after $18 ms injection (40 A), which is $25% of the core electron density (n e0 $ 1 Â 10 19 m À3 ). In reality, however, the core fast ion density is expected to be below the classical prediction, as instabilities occur $2:5 ms after beam injection (Sec.…”
Section: A Fast-ion Distribution Modelingmentioning
confidence: 68%
“…We note in passing that the kinetic stress has been linked directly to plasma rotation by studies on the Madison Symmetric Torus reversal field pinch [33,34]. By a combination of probes and polarimetry, Ding et al [33] demonstrated a clear correlation between the divergence of the measured kinetic stress and the mean u profile (see Figure 2.…”
Section: Introduction and Basic Physicsmentioning
confidence: 89%
“…The paper is focused on the reversed-field pinch (RFP) configuration [1]. Numerical solution of such visco-resistive MHD model applied to the RFP predicted that the magnetic field can acquire a helical state in a self-organized manner [2][3][4][5][6], a feature later observed in high-current plasmas in various RFPs devices [7][8][9]. More recently, the MHD model has improved its descriptive capability of the typical experimental intermittency [10], predicted new ways for channeling helical self-organization towards a selected state highlighting the role of small edge helical magnetic field [11], a set of results then validated by experiments [12] in RFX-mod in Italy.…”
Section: Introductionmentioning
confidence: 99%